1997
DOI: 10.1002/clc.4960200711
|View full text |Cite
|
Sign up to set email alerts
|

Atrial fibrillation: A review of mechanism, etiology, and therapy

Abstract: Summary:The prevalence of elderly individuals in the populations of developed countries is increasing rapidly, and atrial tibrillation (AF) is quite common in these elderly patients: currently, 11 % of the U.S. population is between the ages of 65 and 85 years; 70% of people with AF are between the ages of 65 and 8.5 years. AF causes symptoms secondary to hemodynamic derangements that are the result of increased ventricular response and loss of atrial booster function. AF can lead to reversible impairment of l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
18
0
3

Year Published

1998
1998
2005
2005

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 54 publications
(22 citation statements)
references
References 52 publications
1
18
0
3
Order By: Relevance
“…25 Amiodarone is highly effective in maintaining sinus rhythm; initial fears about toxicity have been tempered because that toxicity is in large part a function of dosage, and atrial fibrillation is being treated with a relatively low dosage. 21 …”
Section: Continued On Next Pagementioning
confidence: 99%
See 1 more Smart Citation
“…25 Amiodarone is highly effective in maintaining sinus rhythm; initial fears about toxicity have been tempered because that toxicity is in large part a function of dosage, and atrial fibrillation is being treated with a relatively low dosage. 21 …”
Section: Continued On Next Pagementioning
confidence: 99%
“…[21][22][23] In this study, we considered a variety of strategies for the treatment of atrial fibrillation but focus on 3 antiarrhythmic drugs, reflecting their common use in the last decade. 21,22,24 Quinidine is still widely used, although possibly decreasing in popularity. 25 Sotalol hydrochloride is generally well tolerated and is widely used for treatment of atrial fibrillation in Europe and Canada.…”
Section: Continued On Next Pagementioning
confidence: 99%
“…From 1987 to 1989, the Framingham population demonstrated a 7.8% prevalence of AF in men aged 65 to 74; the corresponding prevalence in men aged 75 to 84 was 11.7%. Thus, the prevalence of AF is increasing markedly in industrialized nations secondary to growth in the population of elderly individuals in these societies [1][2][3]. However, even the age-adjusted prevalence of AF has increased recently, suggesting that age alone does not account for all of the increased frequency with which physicians are encountering patients with this arrhythmia [3].…”
mentioning
confidence: 97%
“…For instance, therapy with digoxin does not prevent recurrent episodes of AF although β-blocker administration can accomplish this goal [2,5]. Idiopathic or "lone" AF is not as benign an entity as once thought; Jouven et al [6] observed a fourfold increase in cardiovascular mortality and a twofold increase in all cause mortality for middleaged Frenchmen with lone AF.…”
mentioning
confidence: 98%
See 1 more Smart Citation